National and cultural realias of translations into tatar - ŞAHİN, LİAİSAN (My University, 2019)
Â© Yerbulatova et al.Purposes: This article is devoted to the study of realityн translation, the identification of the main types and difficulties of translation based on the material of literary works translated from Russian into Tatar. Implication/Application: Among the objective difficulties of the works of Russian writer translation into the Tatar language, one can note the mismatch of Russian and Tatar words or phrases expressing realities. It is especially difficult to translate those words and expressions that are close in meaning, but differ in \"volume\". Results: The authors show the dependence of translation strategy choice on external sociocultural and pragmatic factors. The study also found out what problems may arise during the transfer of realities in translation, and the main difficulties are highlighted that arise during the translation of realities, in particular, during the absence of an equivalent, correspondence or analogue in the translated language, the need to convey not only the meaning of reality but also its color. Novelty: In our work, the essence of the realities was determined, the main aspects of reality transfer during translation were analyzed, the types of correspondences by a value between the realities, which can be grouped into three main ones, are considered: full, partial correspondence and its absence.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Genel Sosyal Bilimler; General Arts and Humanities; Social Sciences & Humanities; General Social Sciences; Equivalent Translation; National-cultural Specificity; Realities; Translation; Realities; National-cultural Specificity; Equivalent Translation